2020
DOI: 10.1093/nutrit/nuaa035
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the links between consumer food waste, nutrition, and environmental sustainability: a narrative review

Abstract: Emerging research demonstrates unexpected relationships between food waste, nutrition, and environmental sustainability that should be considered when developing waste reduction strategies. In this narrative review, we synthesize these linkages and the evidence related to drivers of food waste and reduction strategies at the consumer level in the United States. Higher diet quality is associated with greater food waste, which results in significant quantities of wasted resources (e.g., energy, fertilizer) and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 75 publications
1
33
0
Order By: Relevance
“…We demonstrate that FAFH is less healthy than FAH and represents approximately one-half of the share of total food spending, and others have recently demonstrated that food waste accounts for nearly 30 % of food spending overall and within FAH and FAFH (16) . Taken together, these findings highlight the need for practitioners to help their clients develop effective strategies to prepare FAH and reduce waste (especially fruits and vegetables) (49) to improve diet quality and reduce spending. Our results demonstrate that decreased spending on non-alcoholic beverages like sugar-sweetened beverages may be an effective step towards improving diet quality.…”
Section: Discussionmentioning
confidence: 88%
“…We demonstrate that FAFH is less healthy than FAH and represents approximately one-half of the share of total food spending, and others have recently demonstrated that food waste accounts for nearly 30 % of food spending overall and within FAH and FAFH (16) . Taken together, these findings highlight the need for practitioners to help their clients develop effective strategies to prepare FAH and reduce waste (especially fruits and vegetables) (49) to improve diet quality and reduce spending. Our results demonstrate that decreased spending on non-alcoholic beverages like sugar-sweetened beverages may be an effective step towards improving diet quality.…”
Section: Discussionmentioning
confidence: 88%
“…A range of publication types were included in this review, including 10 cross-sectional studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], one review [ 68 ], two systematic reviews [ 69 , 70 ], two case studies [ 71 , 72 ], seven intervention studies (three non-randomized controlled trials [ 73 , 74 , 75 ], one randomized controlled trial [ 76 ], three pre-post-design studies [ 77 , 78 , 79 ]), one observational study [ 80 ], one comparative analysis [ 81 ], one critical evaluation [ 82 ], one time series [ 83 ], one multi-method study [ 84 ], and six food-based dietary guidelines [ 85 , 86 , 87 , 88 , 89 , 90 ]. Four main concepts were mapped from the resulting data ( Figure 3 ), and the publications were grouped into these concepts as appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…The link between diet quality and food waste was assessed in three studies [ 59 , 64 , 68 ]. Three studies assessed diet quality using the Healthy Eating Index 2015 (HEI-2015) [ 59 , 60 , 64 ], with one of these studies also using the Alternative Health Eating Index 2010 (AHEI-2010) as a comparison [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, continued improvements to the efficiency of agricultural production will need to be accompanied by reductions in food waste throughout the food system, including in the home, irrespective of the nature of any dietary changes that are made. However, there is the potential for undesirable effects if dietary change in fact drives an increase in food waste (Conrad & Blackstone, 2021), particularly with respect to water footprint associated with greater wastage of plant‐derived foods (Helander et al, 2021).…”
Section: Summary and Recommendationsmentioning
confidence: 99%